Source data for "Diel variability of CO2 emissions from Northern lakes and the effect of lake mixing" - Rudberg, David; Thanh Duc, Nguyen; Schenk, Jonathan; Sieczko, Anna Katarzyna; Pajala, Gustav; Sawakuchi, Henrique Oliveira; Verheijen, Hendricus; Melak, John; MacIntyre, Sally; Karlsson, Jan; Bastviken, David (Linköping University, 2020)
Excel-file with data for reproducing figures and tables for the article and supplementary information.

The dataset was originally published in DiVA and moved to SND in 2024.

Excel-fil med data för återgivning av figurer och tabeller för artikel samt kompletterande information.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Source data for "Diel variability of CO2 emissions from Northern lakes and the effect of lake mixing"
Keywords: environmental sciences; miljövetenskaper; Environmental Sciences; Miljövetenskap